Konsep Diri Matematis Mahasiswa: Tingkatan Kelas dan Latar Belakang Sekolah - Siregar, Nurdiana; Siregar, Nurkhairunnisa (STKIP Andi Matappa Pangkep, 2024)
Mathematical self-concept is a description of knowledge about one's abilities, which can influence one's achievement in learning and teacher performance.This research aims to describe students' mathematical self-concept in terms of grade level and school background. Mathematics is taught to students up to semester 4, so the population in this study was level I and level II students as many as 401 people with a sample of 200 people. The instrument used is a mathematical self-concept scale consisting of 30 statements. Data were analyzed using descriptive analysis techniques using a normal curve approach. The results of the research showed that the average mathematical self-concept for Level I students from MA schools was 74.71 in the medium category, from Islamic boarding schools, it was 74.52 in the medium category, and from high school, it was 75.56 in the medium category, while for Level II students from MA schools, it was 74.88. medium category, Islamic boarding school obtained 74.42 in the medium category, and SMA obtained 75.43 in the medium category.